Supremacia judicial e diálogos constitucionais: deve haver um intérprete final da Constituição Federal? - Piton, Marcelo Martins (2023)
This dissertation is part of the research line of the Masters in Law of Stricto Sensu Postgraduate Program at the Faculty of Law University of Step Deep. The problem faced boils down to the following question: is there a need of a final interpreter of the Federal Constitution? As hypotheses, it is analyzed whether it is justifiable for the Judiciary to have the last word in this matter or if the function Interpretation must also be carried out by the other Powers and civil society, involving effective and permanent interaction. The first specific objective encompasses the analysis of the English and French models of parliamentary supremacy and the American models and Austrian constitutionality control, which give rise to judicial supremacy, its evolutions, implications and controversies. Furthermore, it addresses the Brazilian model, notably the history, formation and performance of the Federal Supreme Court after the Constitution Federal Law of 1988. The second objective is the analysis of institutional capabilities and effects systemic aspects of the Judiciary and Legislative Powers and their decisions.